Clinical applications and therapeutic potentials of advanced nanoparticles: a comprehensive review on completed human clinical trials - Kumarasamy, Ranil Vikraman; Natarajan, Prabhu Manickam; Umapathy, Vidhya Rekha; Roy, Jeane Rebecca; Mironescu, Monica; Palanisamy, Chella Perumal (Frontiers in Nanotechnology, 2024)
Nanoparticles have become known asare attractive therapeutic tools due to their distinctive characteristics, including more accurate drug delivery, improved bioavailability, and enhanced targeted therapy. This review offers a comprehensive analysis of the therapeutic potentials of cutting-edge nanoparticles as demonstrated in human clinical trials, based on empirical evidence. Through systematic searches of major scientific databases, relevant studies published up to March 2024 were included, focusing on clinical trials utilizing advanced nanoparticles for therapeutic purposes. The review comprehensively discusses the diverse applications of nanoparticles in oncology, infectious diseases, neurology, and other medical fields. Additionally, it scrutinizes the safety profiles, efficacy outcomes, and challenges associated with nanoparticle-based therapies. The findings underscore significant progress in translating nanoparticle research into clinical practice and highlight the potential of these innovative platforms to revolutionize medical treatments. This review contributes valuable insights into the growing field of nanoparticle-based therapeutics, fostering a deeper understanding of their clinical applications and implications for in medical practice.